Development process and cognitive testing of CARATkids - Control of Allergic Rhinitis and Asthma Test for children - Borrego, Luís M. (2022)
Funding Information: The authors would like to thank the children and caregivers and the physicians that participated in the study and the Sociedade Portuguesa de Alerglogia e Imunologia Clínica and Associação Portuguesa de Asmáticos e Alérgicos for the help and support the CARAT project. The consensus meetings had logistic and unrestricted financial support from MSD Portugal.